(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تهدف الدراسة إلى وصف البيئة الشاطئية لموقع البحيص في منطقة جبلة, والتعريف بأهم النباتات الموجودة فيها مما يساهم في إضافة المعلومات حول معرفة تنوع البيئات السورية, والتنوع النباتي فيها. أظهرت الدراسة وجود تنوع نباتي محدود وانعدام التطبيق النباتي نظراً للظروف البيئية القاسية في الموقع, وإن النباتات التي عثر عليها بالموقع المدروس هي المسيطرة بحيث تشكل المجتمع الذروي لذلك يحدث لها استبدال ذاتي أو ما يعرف بالتعاقب الذاتي Autosuccession . أخيراً اقترحنا أن يتم إجراء دراسات معمقة لمثل هذا الموقع للوقوف على التفاصيل المتعلقة بعملية التقييم والتصنيف للنباتات الأكثر تردداً في هذه المناطق والاستفادة منها في المجال البيئي والاقتصادي. This study aims to describe the coastal environment of Al – Bhes region at Jableh, and identify the most important plants there. It seeks to contribute new information about the variety of Syrian environment and the various plants in it. The study showed there were a limited plant variety, and nihility of layering plant there due to hard environment conditions in the place. The plants discovered in the studied site are so dominant that they form the climates of plant groups. They undergo a kind of self replacement or what is called Autosuccession. Finally, we suggest a detailed study of such region to evaluate and classify the plants in these places, and make use of the economical and environ mental domains.